Performance of multi-layer perceptron-neural network versus random forest regression for sea level rise prediction - Muslim T.O.B.; Ahmed A.N.; Malek M.A. (Thai Society of Higher Eduation Institutes on Environment, 2023)
artificial intelligence; artificial neural network; error analysis; hydrological cycle; performance assessment; prediction; sea level change; sensitivity analysis; wind direction; Malaysia